1 Records of the Colony of Rhode Island and Providence Plantations, in New England 79–80 (John Russell Bartlett ed., 1856) - (:unkn) unknown (My University, 1643)
reiterated an earlier order "for every man to have so much powder, and so many bullets, and so the forwarning is to stand still in force; and also that every man do come armed unto the meeting upon every sixth day"
Keywords: REQUIRED POSSESSION